Photochromism of the synthetic 4',7-dihydroxyflavylium chloride - Figueiredo, Paulo (2012)
The synthetic compound 4',7-dihydroxyflavylium chloride shows an interesting photochronic effect at moderately acidic pHvalues. Pale yellow solutions of this compound, equilibrated in the dark atpH3.4, become bright yellow upon irradiation with 313-nm light. Switching off the light, gives back the initial pale yellow solution. Photochemical methods, 1H NMR, and molecular orbital calculations were used to elucidate this photochronic behavior. In solutions equilibrated in the dark (pH<5.7), the existence of two main species in equilibrium is demonstrated: the colored flavylium cation and the colorless trans-chalcone. Freshly prepared solutions of this compound at pH6.2 reveal the existance of another colored form, the equinonoidal base, which reacts thermally to yeld trans-chalcone. An analogous reaction takes place in freshly prepared solutions at pH3.4: the flavylium cation is partially converted into trans-chalcone. The extent of such convertion is pH dependent and nearly complete at pH 6.2. Irradiation of thans-chalcone at the wavelenght of 313 nm partially gives back the initial colored form, with concomitant farmation of small amounts of photodegradation produts. The turnover of the photochromic reaction is greater at pH 3.4 than at pH 6.2. The photochromism is explained on the basis of a trans-cis phtoisomerization. In fact the relative stability of the two chalcone isomers is reversed in the excited state, as predicted from molecular orbital calculations.